Lonesome hacker blues. - Wing, Michael (Software engineering notes.)
I'm sitting in my office, daydreaming. My friends are out skiing this weekend, but I promised to come in and fix this custom control, so it can be tested for shipment next week. The product managers told me about it at 5 last night.